Cracking phenomena in automotive wheels: An insight. (November 2019) - Dey, Arthita; Jugade, Hrishikesh; Jain, Vaibav; Adhikary, Manashi
Abstract: In an automotive, wheels form a very critical and important part with respect to application. Wheels with as less number of flaws as possible are a must to make them fit for application in field. The norms of wheel quality parameters are becoming stringent day by day, thereby increasing the onus on raw material suppliers i.e. – steelmakers to improve the soundness of sheet steel. During their manufacturing (through cold forming, welding etc. of hot rolled sheets) cracking of wheel rim or disc is a major issue encountered at the production line. Surface crack, bore crack and flange crack are common types of failures which lead to rejection. This paper discusses a compilation of metallurgical studies of various such defects and their probable root causes, as conducted by authors. Metallography and advanced characterization techniques have been used in analysing the root cause of the defects. Presence of non-metallic foreign material in steel is one of the major causes leading to surface cracks in wheels. In some cases, it has been found that segregation of elements like Carbon, Phosphorous in steel sheets can lead to poor performance of material during deep drawing or forming at the wheel-maker's end. There are also evidences that bad shearing process at the wheel maker's end can also initiate cracking in wheel. Highlights: Low carbon hot rolled steel sheet with or without micro alloying are used for manufacturing wheel of light and medium commercial vehicles. Wheel Disc and Rim are produced in separate production lines by cold forming process and subsequently welded together in an assembly line to manufacture the complete wheel. Cold forming requires formability which is imparted in the steel by meticulously designing the chemistry of the parent steel and controlling the process parameters during hot rolling of the steel. Cracking of wheel disc or rim at the production line poses to be the major problem during manufacturing and forming of the strips. The general cracking phenomenon in wheel disc and rim have been represented as different cases in the current study. The cracking originates from inherent material defect which raised from problems associated to casting or rolling process at steel maker's end. However improper conditions in the downstream process, that is use of improper tool or dies or inappropriate welding process in the disc or rim production line can also create quality issue. Six different cases of failure investigation had been presented in the current paper to highlight what are the common types of failure in the field of wheel rim and disc.